Water quality on coffee farms in the Coatepec region, Veracruz, Mexico - Arrechea-Villacampa, Antonio (2026)
Introduction. Water used in the food industry must be potable; therefore, its analysis is a vital process to ensure compliance with safety standards. Objective. To evaluate the quality of water used in coffee processing on coffee farms in Coatepec, Veracruz, Mexico. Materials and methods. The study was conducted on 14 coffee farms in Coatepec, Veracruz, Mexico, selected based on availability to participate, during October, November, and December 2024. At each site, three samples of the water used for coffee processing were collected, for a total of 42 samples. A multitest kit and reactive strips were used to quantify total dissolved solids (TDS), chemical oxygen demand (COD), total organic carbon (TOC), electrical conductivity (EC), pH, total alkalinity, hydrocyanic acid (HCN), nitrates, nitrites, and copper. Coliform determinations were also performed. SPSS version 25 was used to perform descriptive statistics and comparisons among farms (p < 0.05). Results. The waters showed an average pH of 6.8 and low levels of TDS (44.2 mg/L), nitrates (4.3 mg/L), EC (87.3 µS/cm), total alkalinity (15.4 mg/L), copper (0.14 mg/L), and HCN (0.004 mg/L). The concentrations of TOC and COD were 2.67 and 3.59 mg/L, respectively. In 57 % of the study sites, nitrite values exceeded those established in current legislation; additionally, coliforms were detected in 29 % of the samples. Conclusions. A substantial proportion of the water used in coffee processing did not meet the quality criteria required for human consumption, highlighting the need to establish controls in this process to avoid compromising the final product.